2022
DOI: 10.25105/ijca.v4i2.14153
|View full text |Cite
|
Sign up to set email alerts
|

Debt Policy, Sales Growth, Tax Avoidance: The Moderating Role of Independent Commissioners

Abstract: This study examines the effect of debt policy and sales growth on tax avoidance. In addition, this study examines the role of the independent commissioner as a moderating variable in the relationship between the independent and dependent variables. The method employed in this study is quantitative. This study uses secondary data with the annual financial statements of mining sector companies listed on the Indonesia Stock Exchange for 2018-2020. Research data is sourced from www.idx.co.id and the company's offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Current ETR = Current Tax Expense Income Before Tax Tax avoidance is derived by Current ETR multiplied by -1 as Amalia & Firmansyah (2022) and Rahma & Firmansyah (2022). Executive compensation is the total cash the board of directors, commissioners, and key management receives for a year (Apsari & Supadmi, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current ETR = Current Tax Expense Income Before Tax Tax avoidance is derived by Current ETR multiplied by -1 as Amalia & Firmansyah (2022) and Rahma & Firmansyah (2022). Executive compensation is the total cash the board of directors, commissioners, and key management receives for a year (Apsari & Supadmi, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Independent commissioners are expected to reduce tax avoidance activities by managers to increase compensation as company executives. H3: Independent commissioner weakens the positive effect of executive compensation and tax avoidance Establishing an independent commissioner is one way to reduce managers' acts conflicting with shareholders' interests (Amalia & Firmansyah, 2022). Independent commissioners have experience disciplining managers' performance (Rahma & Firmansyah, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When a company has higher debt, the company can take advantage of the high-interest expense to lower the company's tax expenses (Pajriansyah & Firmansyah, 2017). (Amalia & Firmansyah, 2022;Yulianty et al, 2021) found that debt policy is positively associated with tax avoidance. On the other side, income smoothing actions are carried out by companies with higher debt levels in their capital structure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tax avoidance is tax planning to reduce the tax expenses on the government. Tax avoidance motives can be carried out because the company is in greater debt (Amalia & Firmansyah, 2022;Yulianty et al, 2021). Debt can be used for thin capitalization to increase margins.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring the credibility of reports and improving company's reputation are essential in the current business landscape (Amalia & Firmansyah, 2022;Verawati, 2019). Consequently, companies often seek assurance on the information presented in sustainability reports (Hermawan & Septiani, 2022).…”
Section: Introductionmentioning
confidence: 99%